2016
DOI: 10.1016/j.bbi.2016.07.155
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine treatment affects the inflammatory response and microglial function according to the quality of the living environment

Abstract: It has been hypothesized that selective serotonin reuptake inhibitors (SSRIs), the most common treatment for major depression, affect mood through changes in immune function. However, the effects of SSRIs on inflammatory response are contradictory since these act either as anti-or pro-inflammatory drugs. Previous experimental and clinical studies showed that the quality of the living environment moderates the outcome of antidepressant treatment. Therefore, we hypothesized that the interplay between SSRIs and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 85 publications
5
64
0
Order By: Relevance
“…As a further consequence, SSRIs are expected to amplify the influence of living conditions on mood in a dose-dependent manner. Such hypothesis is supported by preclinical data 3, 4, 5 showing that fluoxetine treatment leads to an improvement of the depression-like phenotype when administered in an enriched condition, while it leads to a worsening when administered in a stressful condition. In addition, SSRI treatment consequences on selected end points, such as vulnerability to obesity, have been shown to be dependent on the quality of the environment.…”
Section: Introductionmentioning
confidence: 83%
“…As a further consequence, SSRIs are expected to amplify the influence of living conditions on mood in a dose-dependent manner. Such hypothesis is supported by preclinical data 3, 4, 5 showing that fluoxetine treatment leads to an improvement of the depression-like phenotype when administered in an enriched condition, while it leads to a worsening when administered in a stressful condition. In addition, SSRI treatment consequences on selected end points, such as vulnerability to obesity, have been shown to be dependent on the quality of the environment.…”
Section: Introductionmentioning
confidence: 83%
“…Additionally, automated segmented axons were overlaid with the thresholded image, and axons that were missed by the automated segmentation were manually traced. The g ‐ratio was estimated by dividing the mean inner diameter by the mean outer diameter of axons in each distance bin . To verify the reasonableness of our estimation, axons were manually traced from one representative image from SW, PW, and sham group and obtained g ‐ratios of 0.46 ± 0.13 ( n = 1348), 0.56 ± 0.10 ( n = 1200), and 0.54 ± 0.08 ( n = 1605), respectively .…”
Section: Methodsmentioning
confidence: 99%
“…This is of great interest as we have reported that fetal and neonatal exposure to fluoxetine increased the proportion of offspring with mild‐to‐moderate NASH (De Long et al, ). Moreover, as fluoxetine has been shown to increase production of IL1β (Alboni et al, ), which is mainly dependent on activation of the NLRP3 inflammasome (Martinon, Burns, & Tschopp, ), these data suggest that the increased prevalence of NASH in offspring born to fluoxetine‐exposed dams may be a result of dysregulated de novo lipogenesis and activation of the NLRP3 inflammasome. Hence, the present study was designed to investigate the effects of fetal and neonatal exposure to fluoxetine on the transcriptional and epigenetic regulation of genes involved in hepatic de novo lipid synthesis and the NLRP3 inflammasome.…”
Section: Introductionmentioning
confidence: 92%